Potential of Painted Terrapin (Batagur borneonsis) Tourism as a Source of Ecotourism Learning - Muhammad Al dilwan (Universitas Pendidikan Indonesia, 2024)
Painted terrapin is a rare species of animal facing extinction. Tourism management based on ecotourism has been implemented to preserve the painted terrapin and improve the local community's economy. Painted terrapin tourism holds the potential as a learning resource, but there is a lack of research on this subject. This research aims to analyze the relevance of painted terrapin tourism as a learning resource for ecotourism. The research was designed using a qualitative method. Data collection techniques included interviews, observations, and literature reviews. Data analysis techniques involved stages of data reduction, data presentation, and data verification. The results of the analysis were presented descriptively, which included reviews of the potential of painted terrapin tourism and its relevance as an ecotourism learning resource. The results indicate that painted terrapin tourism is relevant as a learning resource for ecotourism. This is because the tourism potential, involving observation and educational activities related to the painted terrapin's conditions and ecotourism-based tourism management, aligns with learning objectives. It can effectively support the achievement of learning goals and can be integrated into the educational process.